Clomiphene citrate is associated with favorable cycle characteristics but impaired outcomes of obese women with polycystic ovarian syndrome undergoing ovarian stimulation for in vitro fertilization. Issue 32 (August 2017) - Jiang, Shutian; Kuang, Yanping
Abstract : Abstract: The aim of this study was to explore the effect of clomiphene citrate (CC) on the cycle characteristics and outcomes of obese women with polycystic ovarian syndrome (PCOS) undergoing ovarian stimulation for in vitro fertilization (IVF). This is a retrospective cohort study, and it was conducted at the tertiary-care academic medical center. This study included 174 obese PCOS patients undergoing IVF. In the study group (n = 90), CC and human menopausal gonadotropin (HMG) were administered simultaneously beginning on cycle day 3, while in control group (n = 84) HMG was used only. Both of the 2 groups used medroxyprogesterone acetate (MPA) for preventing premature luteinizing hormone (LH) surges. Ovulation was cotriggered by a GnRH agonist and hCG when dominant follicles matured. The primary outcome measure was the number of oocytes retrieved. Secondary outcomes included the number of top-quality embryos, maturation rate, fertilization rate, cleavage rate, incidence of premature LH surge, and OHSS. The study group received obviously lower total HMG dose [1650 (975–4800) vs 2025 (1350–3300) IU, P = 2.038E–4] but similar HMG duration. While the antral follicle count (AFC) is higher in study group, the number of oocytes retrieved and top-quality embryos are remarkably less [5 (0–30) vs 13 (0–42), P = 6.333E–5; 2 (0–14) vs 3.5 (0–15), P = .003; respectively]. The mature oocyte rate is higher in study group ( P = .036). No significant differences were detected in fertilization rate and cleavage rate between 2 groups. CC has a positive influence on cycle characteristics, but might be correlated with the impaired IVF outcomes (less oocytes retrieved and top quality embryos, lower oocyte retrieval rate) in obese PCOS patients undergoing IVF, when HMG and MPA are used simultaneously.